EFFECT OF LEARNING MODELS INFORMATION SEARCH ON RESULTS LEARN CIVIC EDUCATION STUDENTS CLASS SEVENT AT JUNIOR HIGH SCHOOL PUBLIC THREE KOTO TUO XIII SUB DISTRICTS, KOTO KAMPAR DSTRICTS - Zurvanida '; Sri Erlinda; Ahmad Eddison (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
The observation author in class seventh at Junior High School PublicThree Koto Tuo XIII Sub Districts, Koto Kampar Districts encountered facts orphenomena especially on the lessons Civic Education that of 36 people studentclass seventh at Junior High School Public Three Koto Tuo XIII Sub Districts,Koto Kampar Districts only the results learn obtained students not optimal, it isseen from the test result, students results learn is still at an average grade class56,67 or still below the value KKM which has been established that 70. Modelsinformation search constitute one way that teachers do it turn on subject matterare considered dry. Students seeking the material in groups and answer theteacher’s question to them. (Hisyam Zaini, 2008:48). The research wasconducted in the classroom seventh at Junior High School Public Three Koto TuoXIII Sub Districts, Koto Kampar Districts. The population in this research wereall students class seventh Junior High School Public Three Koto Tuo XIII SubDistricts, Koto Kampar Districts which amounts to 97 people student. The samplein research taken by Purposive sampling. Class of the sample is class VIIb whichamounts to 32 student’s and class VIIc which amount to 32 student’s. So overallis 64 student’s.Based formulation of the problem, in concluded that there is influenceresult learn Civic Education are tough to learning models Information Searchstudent’s class seventh Junior High School Public Three Koto Tuo XIII SubDistricts, Koto Kampar Districts. Based hypothesis testing value ‫ݐ‬௛௜௧௨௡௚ which isgreater than ‫ݐ‬௧௔௕௘௟ at significant level 5% an 1% (5.128 > 1.671) means oninfluence Result Learn Civic Education are tough use learning methodsInformation Search with learning Methods on student class VII Junior HighSchool Public Three Koto Tuo XIII Sub Districts, Koto Kampar Districts. That isto say, that the more often the better implementation are tough to use learningmodels Information Search the better and also high results learn Student’s inClass VII Junior High School Public Three Koto Tuo XIII Sub Districts, KotoKampar DistrictsKeywords : Learning Model Information Search, Results Learn CivicEducation